An Evaluation of World Economic Outlook Growth Forecasts, 2004-17 - Celasun, Oya (IMF Working Papers; Working Paper, 2021)
This paper examines the performance of World Economic Outlook (WEO) growth forecasts for 2004-17. Short-term real GDP growth forecasts over that period exhibit little bias, and their accuracy is broadly similar to those of Consensus Economics forecasts. By contrast, two- to five-year ahead WEO growth forecasts in 2004-17 tend to be upward biased, and in up to half of countries less accurate than a naive forecast given by the average growth rate in the recent past. The analysis suggests that a more efficient use of available information on internal and external factors-such as the estimated output gap, projected terms of trade, and the growth forecasts of major trading partners-can improve the accuracy of some economies' growth forecasts.